2005
DOI: 10.1111/j.1087-0024.2005.200405.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanocyte and Keratinocyte Carcinogenesis: p53 Family Protein Activities and Intersecting mRNA Expression Profiles

Abstract: Melanocytes and keratinocytes were analyzed for potential roles of p53, p73, and p63 tumor suppressor family proteins and of malignancy-specific gene expression changes in the etiology of multi-step cancer. Melanocytes expressed deltaNp73alpha, two p63 isoforms and p53. Although p21 and Noxa mRNA levels increased following DNA damage, p53 family member binding to p21 and Noxa DNA probes was undetectable, suggesting p53 family-independent responses. In contrast, keratinocytes expressed multiple isoforms each of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 69 publications
1
20
1
Order By: Relevance
“…1A, top). Since the p63 antibody is pan-specific, O3C keratinocytes were used as positive control for the p63 isoforms (23,24). Further, when the mRNA levels were examined using semiquantitative RT-PCR with TA-specific p63 primers, little change was observed (less than 0.5-fold) in TAp63 between the ␤TrCP1 ϩ/Ϫ and the ␤TrCP1 Ϫ/Ϫ MEFs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A, top). Since the p63 antibody is pan-specific, O3C keratinocytes were used as positive control for the p63 isoforms (23,24). Further, when the mRNA levels were examined using semiquantitative RT-PCR with TA-specific p63 primers, little change was observed (less than 0.5-fold) in TAp63 between the ␤TrCP1 ϩ/Ϫ and the ␤TrCP1 Ϫ/Ϫ MEFs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While the mechanisms underlying the roles of p63 and p73 in tumor suppression are not yet fully defined, their roles in homeostasis, differentiation and proliferation are indicative of tumor suppressive function. It has been shown that the relationship between p63 and p73 and epithelial carcinogenesis in null mice is consistent with models of sporadic cancer progression to SCC in keratinocyte lineages [39] and with many human tumors that also have reduced expression of p63 and p73 [40][41][42][43][44][45]. While deficiency of these proteins has been characterized in some tumors, overexpression of p63 and p73 isoforms has been found in others [46].…”
Section: P53 In Cancer -C Terminal Role In Structure-specific Dna Binmentioning
confidence: 64%
“…In order to begin to explain isoform-specific activities in tumor suppression, we have taken a global view of all three family members' expression and activities in mouse keratinocyte and melanocyte lineages during carcinogenesis [39]. We examined the total levels of each isoform, their ability to bind to DNA promoters of growth arrest and apoptosis genes, and the induction of downstream effector genes for growth arrest or apoptosis in response to DNA damage signals, i.e.…”
Section: P53 In Cancer -C Terminal Role In Structure-specific Dna Binmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of p63 in melano cytes are conflicting; mouse melanocytes express two isoforms of p63, TAp63 and either TAp63 or Np63 (KuleszMartin et al, 2005), and cultured human eye melanocytes do not ex press TP63 (Kilic et al, 2008). Neither of these studies were adequate biological correlates for human cutaneous melano cytes: mouse melanocytes predominantly reside in the hair fol licle within the dermis, mice do not spontaneously develop melanoma (Bardeesy et al, 2000;Merlino and Noonan, 2003), and the molecular biology of ocular melanoma is distinct from cutaneous melanoma (BelmarLopez et al, 2008;Sato et al, 2008;Shields et al, 2008).…”
mentioning
confidence: 99%